The Development of Islamic Higher Education Quality in Indonesia; Revitalization of The Internal Quality Assurance System - Zaini Tamin AR; Agus Darmawan; Moh Faizin; Siti Aminah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
Accreditation has always been the main goal of improving the quality of Islamic higher education. However, once the accreditation results are announced, the institution no longer pays attention to the Internal Quality Assurance System (IQAS/SPMI). This study aims to analyze this problem as an affirmation that the importance of IQAS for Islamic higher education in Indonesia to be carried out in a style that is most in accordance with the characteristics of a higher education institution. This literature research – with relevant and credible sources – found that IQAS is very important even though the External Quality Assurance System (EQAS/SPME) or accreditation has been decided. IQAS can maintain and improve the quality of the institution in a sustainable manner, which is carried out internally to realize the vision and mission of the institution. In addition, IQAS can meet the needs of stakeholders through the implementation of the Threefold Missions of Higher Education (Tri Dharma Perguruan Tinggi). In IQAS, quality control management is important to be implemented starting from the level of institution, faculties to study programs. Furthermore, the entire academic community must have the same commitment in implementing Islamic higher education quality assurance, so that the quality assurance system can be implemented in stages, systematically and optimally. Keywords: Internal Quality Assurance System, Accreditation, Islamic HigherEducation, Quality Assurance Institution